2021
DOI: 10.1007/s12274-021-3382-3
|View full text |Cite
|
Sign up to set email alerts
|

Docking MOF crystals on graphene support for highly selective electrocatalytic peroxide production

Abstract: Tailoring the reaction kinetics is the central theme of designer electrocatalysts, which enables the selective conversion of abundant and inert atmospheric species into useful products. Here we show a supporting effect in tuning the electrocatalytic kinetics of oxygen reduction reaction (ORR) from four-electron to two-electron mechanism by docking metalloporphyrin-based metal-organic frameworks (MOFs) crystals on graphene support, leading to highly selective peroxide production with faradaic efficiency as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…used Co(NO 3 ) 2 ·6H 2 O as metal source and triglyceride (2‐chloropropyl) phosphate (TCPP) as an organic ligand to prepare MOF@NG catalysts by a solvothermal method. [ 146 ] The authors found that there was a torsion angle of ≈38° between the tetragonal lattice of the cobalt porphyrin MOF and the hexagonal lattice of graphene, which maximized their π‐π interaction, thereby mitigating the mismatch between the metal oxide and grapheme (Figure 16b). Accordingly, the selectivity and FE of the catalyst for H 2 O 2 preparation were 88.2% and 93.4%, respectively.…”
Section: Transition Metal Doped Carbon‐based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…used Co(NO 3 ) 2 ·6H 2 O as metal source and triglyceride (2‐chloropropyl) phosphate (TCPP) as an organic ligand to prepare MOF@NG catalysts by a solvothermal method. [ 146 ] The authors found that there was a torsion angle of ≈38° between the tetragonal lattice of the cobalt porphyrin MOF and the hexagonal lattice of graphene, which maximized their π‐π interaction, thereby mitigating the mismatch between the metal oxide and grapheme (Figure 16b). Accordingly, the selectivity and FE of the catalyst for H 2 O 2 preparation were 88.2% and 93.4%, respectively.…”
Section: Transition Metal Doped Carbon‐based Catalystsmentioning
confidence: 99%
“…Reproduced with permission. [ 146 ] Copyright 2022, Springer. c) Schematic preparation, the yield, and FE of P‐Ni/MC/CP at different voltages.…”
Section: Transition Metal Doped Carbon‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable energy such as solar, wind, geothermal, ocean, and hydrogen energies have emerged as a major global trend today. [9][10][11] As known, the development of unconventional new energy sources cannot be separated from the continuous upgrading of energy storage technologies and equipments. [12][13][14][15] Among numerous emerging energy storage and conversion devices, supercapacitor is a nanoscale energy storage element constructed by using its polarized electrode materials and the ion layer adsorbed on its surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The electrochemical 2e − ORR is a facile and green method of synthesizing H 2 O 2 without any negative byproducts. [12][13][14][15][16][17][18][19] The electrolyte flow typically carries O 2 to the active sites, where it is reduced to H 2 O 2 or H 2 O, corresponding to the 2e − and 4e − ORR pathways, respectively. [20][21][22][23][24][25] An electrocatalyst with high 2e − selectivity is highly required for the production of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%